1997
DOI: 10.1002/hep.510260423
|View full text |Cite
|
Sign up to set email alerts
|

Chlormethiazole inhibition of cytochrome P450 2E1 as assessed by chlorzoxazone hydroxylation in humans

Abstract: Cytochrome P450 2E1 (CYP2E1), an ethanol-inducible Chlormethiazole is a sedative and anticonvulsive drug used form of P450, is active in the metabolism of numerous comin the treatment of alcohol withdrawal. Because it had been pounds. 1 These include endogenous substrates such as acereported that chlormethiazole inhibits the alcohol-inducible tone, 2 organic solvents, 3 procarcinogens (e.g., nitrosacytochrome P450 2E1 in rat liver, we investigated the in vivo mines), 4,5 and therapeutic agents such as chlorzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The final concentration used for each inhibitor was approximately 10-fold its reported K i value to maintain selectivity for its specific CYP isozyme and to obtain at least ≥ 80% inhibition of the reaction. These inhibitors were dissolved in several solvents: 1) in 0.1M potassium phosphate buffer: quinidine, CYP2D6 (4µM) [15], chlomethiazole hydrochloride, CYP 2E1 (120 µM) [16], (+)-nootkatone, CYP2C19 (5µM) [17], phencyclidine hydrochloride, CYP2B6 (100µM) and ticlopidine hydrochloride, CYP2B6 (2µM) [18, 19]; 2) in 0.5% (v/v) ethanol: aminoglutethimide, CYP19 (7µM) [20], sulfaphenazole, CYP2C9 (3µM) [15], α-naphthoflavone, CYP1A1 (0.1µM) [15], ketonconazole, CYP 3A4 (1.8µM) [15] and furafylline, CYP1A2 (8µM) [15]; 3) in 0.3% (v/v) DMSO: trimethoprim, CYP2C8 (320µM) [21] and trans-2-phenylcyclopropyl-amine hydrochloride, CYP2A6 (0.4µM) [22]. Furafylline (the mechanism-based inhibitor) was pre-incubated with hepatic microsomes (0.25 mg) and the NADPH-regeneration system at 37°C for 10 min, and then 50 µM (≈ K m value) of bupropion was added to initiate the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The final concentration used for each inhibitor was approximately 10-fold its reported K i value to maintain selectivity for its specific CYP isozyme and to obtain at least ≥ 80% inhibition of the reaction. These inhibitors were dissolved in several solvents: 1) in 0.1M potassium phosphate buffer: quinidine, CYP2D6 (4µM) [15], chlomethiazole hydrochloride, CYP 2E1 (120 µM) [16], (+)-nootkatone, CYP2C19 (5µM) [17], phencyclidine hydrochloride, CYP2B6 (100µM) and ticlopidine hydrochloride, CYP2B6 (2µM) [18, 19]; 2) in 0.5% (v/v) ethanol: aminoglutethimide, CYP19 (7µM) [20], sulfaphenazole, CYP2C9 (3µM) [15], α-naphthoflavone, CYP1A1 (0.1µM) [15], ketonconazole, CYP 3A4 (1.8µM) [15] and furafylline, CYP1A2 (8µM) [15]; 3) in 0.3% (v/v) DMSO: trimethoprim, CYP2C8 (320µM) [21] and trans-2-phenylcyclopropyl-amine hydrochloride, CYP2A6 (0.4µM) [22]. Furafylline (the mechanism-based inhibitor) was pre-incubated with hepatic microsomes (0.25 mg) and the NADPH-regeneration system at 37°C for 10 min, and then 50 µM (≈ K m value) of bupropion was added to initiate the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the joint effect of alcohol and cellular steatosis on autophagy required CYP2E1 activity in our in vitro model. Generally, this cytochrome P450 is known for its detrimental effects in alcoholic liver disease through free radical formation and lipid peroxidation [ 23 , 54 ]. Therefore, pharmacological inhibition of CYP2E1 has emerged as strategy for treatment of alcohol-induced liver injury [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chlormethiazole was reported to inhibit CYP2E1 transcription as well as CYP2E1 catalytic activity in humans 16 ) . However, one study performed in vivo in rats showed no significant effect of chlormethiazole on CYP2E1 catalytic activity, but showed selective transcriptional suppression of CYP2E1 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…At this dose, chlormethiazole nearly abolished acetaminophen-induced liver injury in mice. Since it was reported that a single administration of 192 mg of chlormethiazole in healthy human controls dramatically inhibits CYP2E1 catalytic activity 16 ) , the dose needed to prevent acetaminophen-induced liver injury may be within the usual therapeutic dose (1.5 g/d) in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation